Peran Ibu Rumah Tangga Buruh Industri Batu Bata dalam Meningkatkan Ekonomi Keluarga Perspektif Ekonomi Islam - Sakti Praja Putra; Romi Adetio Setiawan; Citra Liza (Universitas Muhammadiyah Surabaya, 2026)
This study examines the role of housewives working as laborers in the brick-making home industry in Pagar Dewa Village, South Bengkulu, and their contribution to improving the family economy within the framework of Islamic economics. The phenomenon of dual roles among rural women managing domestic responsibilities while simultaneously engaging in productive income-generating activities is becoming increasingly common, especially in households with limited economic resources. This qualitative research employs purposive sampling to select eight housewives working in the brick industry, supported by observation, semi-structured interviews, and documentation techniques. The findings show that these women significantly contribute to household finances through their wages, which are used to fulfill daily needs, children’s education, food security, and debt relief. Despite facing challenges such as physical exhaustion, time division, and social expectations, the women are able to perform their reproductive and productive roles simultaneously. From the perspective of Islamic economics, their work is categorized as a productive effort (kasb) that aligns with Islamic principles, provided it does not neglect their primary responsibilities at home and is carried out ethically. Their economic contribution also reflects the values of ta’awun (mutual help), maslahah (public benefit), and falah (holistic welfare). This study concludes that the involvement of housewives in the brick industry plays a transformative role in strengthening family resilience and supporting long-term welfare.